Natural Disaster Insurance for Sovereigns : Issues, Challenges and Optimality - Cebotari, Aliona (IMF Working Papers; Working Paper ;, 2020)
Natural disasters are a source of economic risks in many countries, especially in smaller and lower-income states, and ex-ante preparedness is needed to manage the risks. The paper discusses sovereign experience with disaster insurance as a key instrument to mitigate the risks; proposes ways to judge the adequacy of insurance; and considers ways to enhance its use by vulnerable countries. The paper especially aims to inform policy decisions on disaster insurance. Through simulations of natural disasters and various insurance options, we find that sovereign decisions on optimal risk transfer involve balancing trade-offs between growth and debt, based on government risk preferences and country risk exposure. The choice of optimal insurance for smaller countries turns out to be more constrained by cost considerations due to their higher exposure, likely resulting in underinsurance; donor grants could help them achieve a more optimal protection. We also find that optimal insurance packages are those that are least costly relative to expected payouts (i.e. have the lowest insurance multiple), which are also the packages that insure less severe (more frequent) disasters.